By-Laws and Ordinances of the City of Pittsburgh 99 (1828) - (:unkn) unknown (My University, 1816)
Ch. 16, § 1: That if any person or persons shall, within the said city, beat a drum, or without lawful authority, ring any public bell, after sunset, or at any time except in lawful defence of person or property, discharge any gun or fire arms, or play at or throw any metal or stone bullet, or make a bon-fire, or raise or create any false alarm of fire, he, she or they so offending, shall for every such offence, on conviction thereof, forfeit and pay the sum of four dollars32…
Keywords: DISCHARGE